Cryopreserved potato shoot tips showed genotype-specific response to sucrose concentration in rewarming solution (RS) - Vollmer, R.; Villagaray, R.; Castro, M.; Anglin, Noelle L.; Ellis, David (Springer, 2019)
Cryopreservation protocols have been successfully developed for hundreds of species and thousands of genotypes in laboratories around the world. In many of the protocols, the rewarming process occurs in a rewarming solution (RS) with a high concentration of sucrose (0.8–1.2 M). Warming rate and associated conditions influence cell rehydration, loss of accumulated solutes (e.g. cryoprotectants) and recrystallization of small ice crystals in the nuclei. The need for, and effect of, high sucrose concentrations in the RS post-thawing regrowth rate after liquid nitrogen exposure was assessed in the range of 0.0-1.2 M sucrose with a set of 16 potato landraces cryopreserved with the PVS2-droplet vitrification method. The results showed no significant difference for the average recovery rate (81–87%) between sucrose concentrations of 0.3 M to 1.2 M. Fourteen of 16 accessions had their highest recovery rate with sucrose concentrations between 0.3 and 0.9 M. The experimental results were subsequently extended to a genetically diverse set of 85 potato accessions (nine taxa), which demonstrated significantly higher recovery rates of 55–61% with RS sucrose concentrations of 0.3–0.9 M, compared to the sucrose concentrations of 0.0 M (37%) and 1.2 M (44%). Only one of 85 accessions showed its highest recovery rate with the routinely used RS sucrose concentration of 1.2 M. Of all the concentrations tested, 0.6 M sucrose appeared to be the best bet in terms of recovery rates across the genotypes; therefore, our routine protocol has been changed from 1.2 M sucrose to 0.6 M. The specific response to low (0.0 M) and high RS sucrose concentrations (1.2 M) was highly variable within species/subspecies and appears to be genotype specific. Thus, caution should be taken in generalizing experimental cryopreservation results obtained with a limited number of accessions to larger germplasm collections.